Cut It Out : The C-Section Epidemic in America - Morris, Theresa, 1956- (Book collections on Project MUSE., 2013)
Examines the exponential increase in the United States of the most technological form of birth that exists -- the cesarean section -- and challenges most existing explanations of this unprecedented rise, arguing that there is a new culture within medicine that avoids risk or unpredictable outcomes and instead embraces planning and conservative choices, all in an effort to have perfect births.